Efficient computation of adjusted p-values for resampling-based stepdown multiple testing - Romano, Joseph P.; Wolf, Michael (Statistics & probability letters, 2016)
There has been a recent interest in reporting p-values adjusted for the resampling-based stepdown multiple testing procedures proposed in Romano and Wolf (2005a,b). The original papers only describe how to carry out multiple testing at a fixed significance level. Computing adjusted p-values instead in an efficient manner is not entirely trivial. Therefore, this paper fills an apparent gap by detailing such an algorithm.